Processing of masked and unmasked emotional faces under different attentional conditions: an electrophysiological investigation - Zotto, Marzia Del; Pegna, Alan J. (Frontiers in Psychology, 2015)
In order to investigate the interactions between non-spatial selective attention, awareness and emotion processing, we carried out an ERP study using a backward masking paradigm, in which angry, fearful, happy and neutral facial expressions were presented, while participants attempted to detect the presence of one or the other category of facial expressions in the different experimental blocks. ERP results showed that negative emotions enhanced an early N170 response over temporal-occipital leads in both masked and unmasked conditions, independently of selective attention. A later effect arising at the P2 was linked to awareness. Finally, selective attention was found to affect the N2 and N3 components over occipito-parietal leads. Our findings reveal that i) the initial processing of facial expressions arises prior to attention and awareness; ii) attention and awareness give rise to temporally distinct periods of activation independently of the type of emotion with only a partial degree of overlap; and iii) selective attention appears to be influenced by the emotional nature of the stimuli, which in turn impinges on unconscious processing at a very early stage. This study confirms previous reports that negative facial expressions can be processed rapidly, in absence of visual awareness and independently of selective attention. On the other hand, attention and awareness may operate in a synergistic way, depending on task demand.